Use of decision support systems to improve dam planning and dam operation in Africa. - McCartney, Matthew P.; King, Jackie (CGIAR Challenge Program on Water and Food, 2011)
After a hiatus in dam investment, through the 1990s and the early part of this century, construction of large dams is increasing again. Modern decision support systems can usefully input to this process by guiding the analysis of complicated hydrological, environmental, social and economic factors associated with water allocation and assessing the impact of different, often conflicting, management options both in planning and operation of dams. This publication highlights the constructive role that decision support systems can play in planning and operation of dams. It illustrates the importance of considering environmental and social issues in decision making so that positive benefits of large dams can be maximized and the negative impacts minimized.